Analysis of Terpenes in Cannabis sativa L. Using GC/MS: Method Development, Validation, and Application - Ibrahim, Elsayed A.; Wang, Mei; Radwan, Mohamed M.; Wanas, Amira S.; Majumdar, Chandrani G.; Avula, Baharthi; Wang, Yan-Hong; Khan, Ikhlas A.; Chandra, Suman; Lata, Hemant; Hadad, Ghada M.; Abdel Salam, Randa A.; Ibrahim, Amany K.; Ahmed, Safwat A.; ElSohly, Mahmoud A. (Planta Medica, 2019)
Terpenes are the major components of the essential oils present in various Cannabis sativa L. varieties. These compounds are responsible for the distinctive aromas and flavors. Besides the quantification of the cannabinoids, determination of the terpenes in C. sativa strains could be of importance for the plant selection process. At the University of Mississippi, a GC-MS method has been developed and validated for the quantification of terpenes in cannabis plant material, viz., α-pinene, β-pinene, β-myrcene, limonene, terpinolene, linalool, α-terpineol, β-caryophyllene, α-humulene, and caryophyllene oxide. The method was optimized and fully validated according to AOAC (Association of Official Analytical Chemists) guidelines against reference standards of selected terpenes. Samples were prepared by extraction of the plant material with ethyl acetate containing n-tridecane solution (100 µg/mL) as the internal standard. The concentration-response relationship for all analyzed terpenes using the developed method was linear with r2 values > 0.99. The average recoveries for all terpenes in spiked indoor cultivated samples were between 95.0 – 105.7%, with the exception of terpinolene (67 – 70%). The measured repeatability and intermediate precisions (% relative standard deviation) in all varieties ranged from 0.32 to 8.47%. The limit of detection and limit of quantitation for all targeted terpenes were determined to be 0.25 and 0.75 µg/mL, respectively. The proposed method is highly selective, reliable, and accurate and has been applied to the simultaneous determination of these major terpenes in the C. sativa biomass produced by our facility at the University of Mississippi as well as in confiscated marijuana samples.
Keywords: Cannabis sativa; Cannabaceae; terpenes; GC-MS; method development; method validation